2014
DOI: 10.2147/ott.s62707
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary analysis of the risk factors for radiation pneumonitis in patients with non- small-cell lung cancer treated with concurrent erlotinib and thoracic radiotherapy

Abstract: PurposeThe aim of this study was to investigate radiation pneumonitis and its associated risk factors in patients with non-small-cell lung cancer treated with concurrent erlotinib and thoracic radiotherapy.Materials and methodsWe conducted an analysis of patients with nonoperable stage IIIA–IV non-small-cell lung cancer who were treated with concurrent thoracic radiotherapy and erlotinib (ClinicalTrials.gov identifier: NCT00973310). The Common Terminology Criteria for Adverse Events version 3.0 grading system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…Zhuang et al reported that the lung dosimetric parameters and PTV are the predictive factors of RP for patients simultaneously treated with EGFR-TKI and TRT (19). Consistent ndings were observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Zhuang et al reported that the lung dosimetric parameters and PTV are the predictive factors of RP for patients simultaneously treated with EGFR-TKI and TRT (19). Consistent ndings were observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Zhuang et al reported that the lung dosimetric parameters and PTV are the predictive factors of RP for patients simultaneously treated with EGFR-TKI and TRT(19). Consistent ndings were observed in our study.…”
supporting
confidence: 92%
“…Zhuang et al reported that the lung dosimetric parameters and PTV are the predictive factors of RP for patients simultaneously treated with EGFR-TKI and TRT [ 19 ]. Consistent findings were observed in our study.…”
Section: Discussionmentioning
confidence: 99%